Letter - Borough and Poplar Trades Council & Central Labour Party, 11 May 1926 (Poplar)
1926-05-11 "Letter - Borough and Poplar Trades Council & Central Labour Party, 11 May 1926" [g0223001.jpg], 11 May 1926 Local Organisation